Effect of light reaction agility training (LRAT) on agility performance of young male badminton players - Donny Ardy Kusuma; Setiyo Hartoto; Mochamad Purnomo; Agung Robianto; Afif Rusdiawan; Dewangga yudhistira; Muhammad Labib Siena Ar Rasyid; Alfina Diva Pratiwi; Nisa Hamidah Nur Azizah (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The application of technology in sports is increasingly growing, including in badminton.